Workshop Pembuatan Asesmen Numerasi dalam Kurikulum Merdeka bagi Guru Sekolah Dasar - Nur, Iyan Rosita Dewi; Yuliani, Anik; Sopiany, Hanifah Nurus; Sugiono, Darso (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2023)
Assessment is a form of assessment that is used to measure cognitive abilities or student learning outcomes at the primary, secondary and equivalent levels. The minimum competency assessment is used to see how the deficiencies are mapped in learning activities so that improvements can be made in subsequent activities which in the end can obtain the skills or abilities of Indonesian students as a whole. The main objective in carrying out this activity is to improve the ability of teachers to make in-depth assessments of the independent curriculum so that in the end it is expected to improve students' abilities in learning mathematics. This activity was carried out in the form of a workshop with material on training in making assessments in the independent curriculum. This activity involved 25 participants who were elementary school teachers in Curug village, Klari district, Karawang district. This community service activity uses the method of carrying out lectures related to the National Assessment, minimum competency assessment, providing training in compiling assessment questions related to numeracy literacy, assigning assignments, and discussing. -mathematical assessment questions. The response of the workshop participants to the material provided was very good, especially in terms of the urgency of the material, the scope of the training material, the time it was held and the competence of the resource persons. Post-training assistance is carried out 1 time after 3 weeks of workshop activities. Asesmen merupakan salah satu bentuk penilaian yang digunakan dalam mengukur kemampuan kognitif atau hasil belajar siswa di tingkat dasar, menengah dan yang sederajat. Asesmenkompetensi minimum digunakan dalam melihat bagaimana pemetaan kekurangan-kekurangan yang berada di dalam kegiatan pembelajaran sehingga dapat dilakukan perbaikan dalam kegiatan selanjutnya yang pada akhirnya bisa didapatkan kecakapan atau kemampuan siswa Indonesia secara utuh. Tujuan Utama dalam pelaksanaan kegiatan ini yaitu untuk meningkatkan kemampuan para guru membuat asesmendalam kurikulum merdeka sehingga pada akhirnya diharapkan dapat meningkatkan kemampuan siswa dalam belajar matematika. Kegiatan ini dilaksanakan dalam bentuk workshop dengan materi tentang pelatihan pembuatan asesmen dalam kurikulum merdeka. Kegiatan ini melibatkan 25 peserta yang merupakan guru sekolah dasar di desa Curug kecamatan Klari kabupaten Karawang. Kegiatan pengabdian kepada masyarakat ini menggunakan metode pelaksanaan ceramah terkait Asesmen Nasional, asesmen kompetensi minimum, memberikan pelatihan penyusunan soal-soal asesmen terkait literasi numerasi, pemberian tugas, dan diskusi Dari pemberian tugas mandiri yang diberikan kepada peserta, di atas 90% guru mampu menyusun soal-soal asesmen matematika. Respon para peserta workshop terhadap materi yang diberikan sangat bagus, terutama pada segi aspek urgensi materi, cakupan materi pelatihan, waktu penyelenggaraan dan kompetensi narasumber. Pendampingan pasca pelatihan dilakukan 1 kali setelah 3 minggu kegiatan workshop selesai dilaksanakan.